The Effect of Dividend Policy and Profitability on Firm Value: (Case Study of Manufacturing Companies in the Consumer Goods Sector Listed on the Indonesia Stock Exchange in 2017-2021) - Rizki Juliani Putri (Profesional Muda Cendekia Publishing, 2023)
The purpose of this study is to compare Dividend Policy (DPR) and Profitability (ROE) with Firm Value in Manufacturing companies in the Consumer Goods Industry Sector Listed on the Indonesia Stock Exchange in 2017-2021. This research is quantitative and uses secondary data. The population of this study is Manufacturing companies in the Consumer Goods Sector that are listed on the Indonesia Stock Exchange from 2017-2021 using the purposive sampling method and a 5-year observation period totaling 101 samples. The data analysis used is multiple linear regression analysis. The results of this study conclude that partially Dividend Policy (DPR) has a significant negative effect on Firm Value (PBV) and Profitability (ROE) has a significant positive effect on Firm Value (PBV) of 18% and simultaneously Dividend Policy (DPR) and Profitability has a positive effect significant to Firm Value (PBV)